Kesiapan Guru Madrasah Ibtidaiyah dalam Memberikan Psychological First Aid bagi Peserta Didik yang Mengalami Kecemasan - Choerul Anwar Badruttamam; Dwi Rosyidatul Kholidah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Anxiety among elementary school students has become an increasingly prevalent mental health issue that may adversely affect children's social, emotional, and academic development. Madrasah Ibtidaiyah teachers play a strategic role as they interact directly with students on a daily basis; therefore, they need to be adequately prepared to provide Psychological First Aid (PFA) as an initial psychological support intervention. This study aimed to describe the readiness of Madrasah Ibtidaiyah teachers to provide Psychological First Aid for students experiencing anxiety. This study employed a quantitative approach using a descriptive survey design. Data were collected through an online questionnaire administered to 85 Madrasah Ibtidaiyah teachers selected using purposive sampling. The research instrument consisted of 26 questionnaire items covering knowledge of Psychological First Aid, attitudes toward providing PFA, skills in applying the Look, Listen, and Link principles, and factors supporting and hindering teachers' readiness. The data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings revealed that, overall, the readiness of Madrasah Ibtidaiyah teachers to provide Psychological First Aid was categorized as high, with an average percentage of 74.6%. The knowledge aspect achieved 71.8% (high category), the attitude aspect 81.2% (very high category), and the skills aspect 69.5% (high category). Factors supporting teachers' readiness included concern for students' well-being, positive teacher–student relationships, and support from colleagues. Meanwhile, the main barriers identified were limited training on child mental health and Psychological First Aid, insufficient understanding of PFA procedures, and the absence of specific school-based programs supporting students' mental health. Based on these findings, it can be concluded that Madrasah Ibtidaiyah teachers demonstrate a relatively high level of readiness to provide initial psychological support for students experiencing anxiety. Nevertheless, structured training programs, institutional support from madrasahs, and collaboration with mental health professionals are necessary to enhance teachers' competencies in implementing Psychological First Aid effectively.